Effect of Screen Time on Eye Dryness: Doi: 10.36351/pjo.v39i3.1616 - Waseem, Madiha; Hussain, Mehvash; Mengal, Mahtab (Pakistan Journal of Ophthalmology, 2023)
Purpose: To determine the relationship between screen time and dry eye: A hospital based study. Study Design: Cross sectional, observational. Place and Duration of Study: Helper’s eye hospital, Quetta from June 2020 to August 2021. Methods: There were 62 subjects, age 13 – 71 years, either gender with dry eye symptoms, normal anterior and posterior segment and daily use of screen devices such as mobile and laptop. Tear film break-up time was performed in all the patients to confirm dry eye using fluorescein strip. Screen time per day was graded as mild (< 2 hours), moderate (2 – 6 hours) and marked (> 6 hours). Chi square test was performed for data analysis on SPSS version 23 and P≤0.05 was considered statistically significant. Results: Mean age of the patients was 44.34 ± 16.43. There were 66.1% females and 33.9% males. The commonest symptom was itching (35.5%). Tear film break up time test was positive in 37 (59.7%). Out of 18 patients with mild screen time, 10 (55.5 %) subjects had dry eye. Out of the 23 subjects with moderate screen time, 17 (73.9%) had dry eye while out of 21 subjects with severe screen time, 10 (47.6%) had dry eye. The results of our study were not statistically significant with p value 0.189. Conclusion: There is no association between increased screen time and the dry eye. However, care must be taken to prevent the discomfort arising from excessive screen time.